Enabling teachers to explore grade patterns to identify individual needs and promote fairer student assessment - Friedler, Sorelle A.; Tan, Yee Lin; Peer, Nir J.; Shneiderman, Ben (Computers and education, 2008)
Exploring student test, homework, and other assessment scores is a challenge for most teachers, especially when attempting to identify cross-assessment weaknesses and produce final course grades. During the course, teachers need to identify subject weaknesses in order to help students who are struggling with a particular topic. This identification often needs to happen across multiple assessment data points and should be considered in comparison to the class’s progress as a whole. When determining grades, fairness to all is essential, but there are special needs for students who did poorly on one exam or had a steadily increasing grasp of the subject. We present eduViz, a visualization tool designed to help teachers explore and assign grades. Teachers can see the trajectory of student scores, the relationship of a particular student to the class, and use categories they have defined in order to filter their assessment information. Query response is immediate and all logical comparisons are possible. Teachers can easily compare their query to the class or per student average as well as view scores by raw point total or percentage. Additionally, eduViz provides a grade assignment interface which allows teachers to view sorted student scores in a scatterplot. This scatterplot is coupled with a unique partition slider which allows users to move color coordinated bands on the scatterplot to indicate grade ranges. As these grade ranges are set, a histogram is updated to show the number of students assigned to each grade range. These features give teachers new and powerful ways to explore and assign grades so that they can better understand student strengths and weaknesses and make the most of the time they have available. Interviews with 16 expert teachers indicate that eduViz is a success across fields, provides teachers with a useful tool to understand and help their classes, and encourages reflective practice.